2018
DOI: 10.1155/2018/6136075
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DJ-1 Fails to Protect Mitochondrial Complex I Subunit NDUFS3 in the Testes and Contributes to the Asthenozoospermia

Abstract: Asthenozoospermia (AS), an important cause of male infertility, is characterized by reduced sperm motility. Among the aetiologies of AS, inflammation seems to be the main cause. DJ-1, a conserved protein product of the PARK7 gene, is associated with male infertility and plays a role in oxidative stress and inflammation. Although our previous studies showed that a reduction in DJ-1 was accompanied by mitochondrial dysfunction in the sperm of patients with AS, the specific mechanism underlying this association r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Three of them, Ndufs2, Uqcr10, and Cox2, are key mitochondrial electron transport complex proteins specifically involved in complexes I, III, and IV, respectively [45]. DJ-1—a protein deglycase—contributes in the regulation of mitochondrial complex I and it would be involved in the control of oxidative stress [46,47]. Finally, Ogdh is an enzyme of the Krebs cycle that would also be involved in mitochondrial functionality, specifically in ROS generation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Three of them, Ndufs2, Uqcr10, and Cox2, are key mitochondrial electron transport complex proteins specifically involved in complexes I, III, and IV, respectively [45]. DJ-1—a protein deglycase—contributes in the regulation of mitochondrial complex I and it would be involved in the control of oxidative stress [46,47]. Finally, Ogdh is an enzyme of the Krebs cycle that would also be involved in mitochondrial functionality, specifically in ROS generation [48].…”
Section: Discussionmentioning
confidence: 99%
“…The DJ-1 gene belongs to the Thi/PfpI superfamily (Wang et al, 2018), which is located at chromosome 1p36 and encodes a ubiquitous protein consisting of 189 amino acids (Van Duijn et al, 2001). Among its biological functions, the most important is protecting against oxidative stress (Kahle et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our functional analysis revealed four candidate genes highly influenced by the increase of inbreeding. The two most affected genes ( PARK7 and VAMP3 , BTA16, p < 0.0001) have been previously associated with spermatogenesis and sperm maturation in mice models (Sun et al, 2014; Y. Wang et al, 2018) and chicken (Zhang et al, 2017). From these, PARK7 was more associated with mitochondrial function than sperm head shape in rats and human beings (Sun et al, 2014; Y. Wang et al, 2018), suggesting that its role in the reproductive process would be more related to sperm motility than morphometry.…”
Section: Discussionmentioning
confidence: 98%
“…The two most affected genes ( PARK7 and VAMP3 , BTA16, p < 0.0001) have been previously associated with spermatogenesis and sperm maturation in mice models (Sun et al, 2014; Y. Wang et al, 2018) and chicken (Zhang et al, 2017). From these, PARK7 was more associated with mitochondrial function than sperm head shape in rats and human beings (Sun et al, 2014; Y. Wang et al, 2018), suggesting that its role in the reproductive process would be more related to sperm motility than morphometry. In the case of VAMP3 , it encodes a protein with a key function during acrosome formation and capacitation through the development of ternary trans‐SNARE complexes which it was found that modulate the sperm shape in a porcine model (Tsai et al, 2010).…”
Section: Discussionmentioning
confidence: 98%